Chapter Legge e giustizia amministrativa durante il ventennio fascista - MERUSI, FABIO (Studi e saggi, 2021)
The paper focuses on the relationship between the Fascist regime and the administrative justice. Once identified in the "invention" of exclusive jurisdiction (over individual matters) a "revolutionary" act of the early Fascism, the paper faces the problem of the administrative litigation over public debt. The issue is treated starting from the transformation of the jurisdiction of merit in the matter of public debt into exclusive jurisdiction: a special attention is paid to the two opposite theses of the "left-wing fascism" and the Italian Constitutional Court. Subsequently, the reflection shifts to the Fascist laws that have limited or excluded since 1923 the appeal against certain administrative acts, also referring to the reactions of the doctrine of the time. A particular case concerns the vice of excess of power which, in the Fascist period, was rationalized and also took on a different meaning from the original one foreseen by the law of 1889. After the fall of Fascism, a final look is turned to the two elusive techniques of the appeal to the administrative judge represented by the laws-measure and the so called "theft of jurisdiction"